Adhesion - deformation and dynamic processes in boundary layers / A. Stelmakh // Problems of Tribology. – 2012. – № 1. – Р. 106-112. - Стельмах, А.У. (Problems of Tribology, 2014)
On the base of investigation of the regularities of both pressure and boundary layer phase (liquid, liquid-gas mixture) changing along the lubricant feed axis within three working linear contact sliding areas (convergent—transitional—divergent) the physical DPBL model has been proposed. The latter establishes the correlation between dynamic processes and tribological unit behavior.